2017
DOI: 10.56093/ijans.v87i11.75892
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of increasing dietary levels of raw lentil seeds on meat fatty acid and plasma metabolic profile in broiler chickens

Abstract: The aim of the present study was to investigate the effect of diets containing raw lentil seeds (Lens culinaris cv. Eston and cv. Anicia) on meat fatty acids profile and blood plasma parameters of broiler chickens. Day old, broiler chicks (1,000; Cobb 500) were randomly allocated to the following 5 treatments, viz. a diet based on corn and SBM as control; 200g/kg of raw lentil seeds cv. Eston (LE); 400 g/kg of LE; 200g/kg of raw lentil seeds cv. Anicia (LA);400 g/kg of LA. Data were analysed as a 2 × 2 factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
6
9
0
Order By: Relevance
“…We have to note that competitiveness of crop production depends on a number of different factors, including elements of growing technology. Our research results are consistent with other literature data presented for Romanian, Canadian and Polish genotypes [Ciurescu et al, 2016;Krzyżaniak et al, 2019;Zając et al, 2020], while they provided higher rates in protein and fat, but slightly lower index in fiber for Italian genotype [Peiretti & Meineri, 2007]. Ciurescu [2016] observed similar protein, fat, and ash content to those found in our studies, but with lower fiber content (about 11%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We have to note that competitiveness of crop production depends on a number of different factors, including elements of growing technology. Our research results are consistent with other literature data presented for Romanian, Canadian and Polish genotypes [Ciurescu et al, 2016;Krzyżaniak et al, 2019;Zając et al, 2020], while they provided higher rates in protein and fat, but slightly lower index in fiber for Italian genotype [Peiretti & Meineri, 2007]. Ciurescu [2016] observed similar protein, fat, and ash content to those found in our studies, but with lower fiber content (about 11%).…”
Section: Resultssupporting
confidence: 93%
“…Our research results are consistent with other literature data presented for Romanian, Canadian and Polish genotypes [Ciurescu et al, 2016;Krzyżaniak et al, 2019;Zając et al, 2020], while they provided higher rates in protein and fat, but slightly lower index in fiber for Italian genotype [Peiretti & Meineri, 2007]. Ciurescu [2016] observed similar protein, fat, and ash content to those found in our studies, but with lower fiber content (about 11%). Zhang [2021] evaluated the quality of two Camelina sativa varieties grown under different climatic conditions in different locations of China and reported that protein and fat contents were in Obtained results on determining coefficients of energy, integral evaluation and complex coefficient of competitiveness showed that they change depending on the studied factors (Table 3).…”
Section: Resultssupporting
confidence: 93%
“…TA B L E 1 3 Effects of different sources and levels of Camelina sativa on ascites index (% of live weight) at day 42 and ascites mortality of broiler chickens during production period. The inclusion of different sources or levels of camelina in diets, except 2% CO, decreased growth performance in broilers, which are in agreement with former studies (Ciurescu et al, 2016;Thacker & Widyaratne, 2012). In contrast to our finding, Jaśkiewicz et al (2014) have reported that the inclusion of CO in the diet had no detrimental effect on broiler performance.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to our finding, Jaśkiewicz et al (2014) have reported that the inclusion of CO in the diet had no detrimental effect on broiler performance. Ciurescu et al (2016) also showed that diets with 5% CS or 2.5% CO did not have negative effect on broiler performance. However, BWG significantly decreased in birds that received a diet containing 10% CS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation